Clinical Characteristics and Prognoses of Patients With Systemic Lupus Erythematosus Hospitalized for Pulmonary Infections - Yang, Yanli; Jiang, Hui; Wang, Chuhan; Jiang, Nan; Wu, Chanyuan; Zhang, Shangzhu; Jiang, Wei; Peng, Jinmin; Weng, Li; Zhao, Jiuliang; Wang, Qian; Li, Mengtao; et al. (Frontiers in Medicine, 2021)
Background: This single-center study examined factors associated with mortality in SLE patients who were hospitalized with pulmonary infections (PIs). Methods: The clinical data of 95 SLE patients from a single institution in China who were hospitalized for PIs were retrospectively analyzed. Multivariate Cox regression and survival analyses were performed to identify factors associated with mortality. Results: There were 14 males (15%) and 81 females (85%), and 33 patients (34%) died during follow-up. The survivors and non-survivors had significant differences in neutrophil count, immunoglobulin G (IgG), serum creatinine, serum albumin, proteinuria, cardiopulmonary involvement, SLE disease activity index (SLEDAI), and prevalence of opportunistic infections (all p<0.05), but no significant differences in age, disease duration, lymphocyte count, complement levels, anti-dsDNA antibody positivity, diabetic complications, bacterial infections, or use of a corticosteroid or immunosuppressive therapy (all p>0.05). Multivariate Cox regression analysis showed that cardiopulmonary involvement (HR 2.077，95%CI（1.022-4.220），p=0.043), and opportunistic infection (HR 2.572，95%CI(1.104-5.993)，p=0.029) were independent risk factors for 120-day mortality. Use of high-dose steroid pulse therapy (HR: 0.982; 95%CI: 0.410–2.350; p=0.982) or a first-line immunosuppressant (HR: 1.635; 95%CI: 0.755–3.542, p=0.212) had no effect. Conclusion: Cardiopulmonary involvement and opportunistic infection were independent risk factors for mortality in SLE patients who were hospitalized for PIs. High-dose pulse steroid therapy and immunosuppressive therapy did not affect mortality.